2022
DOI: 10.54783/ijsoc.v4i1.429
|View full text |Cite
|
Sign up to set email alerts
|

Human Resources Performance Improvement Through Training During the Covid-19 Pandemic

Abstract: For human resource management, making improvements to human resources is one of the essential factors to be able to improve and optimize company performance. This increase can then be carried out through the implementation of training, including during the Covid-19 pandemic. This research will then try to see how the performance of human resources can be improved through the implementation of training during the Covid-19 pandemic. This research will be carried out using a qualitative approach as the research m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…They also do not feel the benefits of online learning over face-to-face learning. It is following research conducted by (Lubis & Lubis, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also do not feel the benefits of online learning over face-to-face learning. It is following research conducted by (Lubis & Lubis, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing benefits, online learning is also considered detrimental to children in gaining knowledge. The Lubis and Lubis, (2020) study measured parents' perceptions of online learning during the COVID-19 pandemic. The results of their study showed that overall, parents were not satisfied with the implementation of E-Learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Covid-19 epidemic also emerged in China and soon affected the whole world. As a result of this global epidemic, countries have also affected each other economically (Lubis, 2023). When analyzed in the context of the classification in the table, while there was a 2.8% growth worldwide in 2019, a negative growth of -3.1% was experienced in 2020 as a result of the measures taken due to the Covid-19 outbreak.…”
Section: Effects Of the Covid-19 Pandemic On Economic Growth In The L...mentioning
confidence: 99%